If 5x-11y = 2x+5y,  then find the value of 3x² + 2y² : 3x² - 2y²



Asked on

3 Answers | Add Yours

isbeatbox's profile pic

Posted on (Answer #1)

ok lets start

5x-11y=2x+5y                3x^2+2y^2:3x^2-2y^2

3x-11y=5y                     3x^2+2y^2:3x^2-2y^2

3x=16y                          3x^2+2y^2:3x^2-2y^2

x= 5.333...yor  5+1/3y      3x^2+2y^2:3x^2-2y^2






y:y   or 1:1

hope this helps

neela's profile pic

Posted on (Answer #2)

By data : 5x-11y=2x+5y

To find the ratio, 3x² + 2y² : 3x² - 2y²


5x -11y=2x+5y Or

5x-2x= 5y+11y=16y Or

3x=16y Or

x=(16/3)y. Therefore,

x^2 = (16y/3)^2. Substituting in 3x² + 2y² : 3x² - 2y², we get:

{3(16y^2/3^2)+2y^2} : {3(16y/3)^2-2y^2}. Multiplying both terms by 3^2, we get the ratio,

We can reduce by y^2 both atecedent and precedent terms of the ratio.

(3*16^2+ 2*3^2)y^2 : (3*16^2-2*3^2)Y^2,

Dividing by y^2, we get:

=3*16^2+ 2*3^2 : 3*16^2-2*3^2

= 786 : 750. Both terms of the ratio could be further reduced by 6 and obtain the ratio as:

=131: 125.



giorgiana1976's profile pic

Posted on (Answer #3)

First of all, let's focus on the first condition given by the ennunciation, namely 5x-11y = 2x+5y.

We'll group the term in "x" into the left side of the equal and the terms in "y" into the right side and we'll do the math:

5x-2x = 11y+5y


For the moment, let's stop in this point of action.

Now,l let's focus on the exression which we have to calculate:

(3x² + 2y²) : (3x² - 2y²)

The expression at numerator, (3x² + 2y²), we could re-write it in this way:

(3x² + 2y²)= (3x + 2y)² - 2*3x*2y

The expression at denominator, (3x² - 2y²), is a difference ofsquares and it could be written as:

(3x² - 2y²)= (3x - 2y)*(3x + 2y)

Now, let's put together the found expressions:

(3x² + 2y²) : (3x² - 2y²)= [(3x + 2y)² - 2*3x*2y]/(3x - 2y)*(3x + 2y)

In the end, let's turn back at the found condition:


We'll apply some tricks on this condition, depending on the last form of the expression which we have to calculate:


3x + 2y=16y+2y

3x + 2y=18y

3x - 2y=16y-2y

3x - 2y=14y

Now, all we have to do is to substitute the calculated expressions above, into our expression:

[(3x + 2y)² - 2*3x*2y]/(3x - 2y)*(3x + 2y)=[(18y)²- 2*16y*2y]/(14y)*(18y)

[(18y)²- 2*16y*2y]/(14y)*(18y)=[(18y)²-2²*4²*y²]/14*18*y²=

But, at the numerator we have again a difference of squares:




After simplifying:

3x² + 2y² : 3x² - 2y²=65/63

We’ve answered 288,375 questions. We can answer yours, too.

Ask a question